(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article focuses on the challenges of learners’ underperformance in Social Studies in Namibia. The study investigated the possible factors that may contribute to learners’ underperformance in Social Studies in the selected schools. The following research question guided the investigation: What are the possible causes of underperformance of learners in Social Studies in Grades 5–7 at primary schools in Namibia? The aim was thus to investigate the possible factors which may contribute to learners’ underperformance in Social Studies. Data were collected from selected teachers and principals via questionnaires and semi-structured interviews, lesson observations and an analysis of appropriate documents. Different data collection methods were used to assure the validity and reliability of the research through triangulation. Triangulation was used through the collection of data by means of questionnaires, interviews, observation, an analysis of relevant documents and a literature review. A number of factors that constitute obstacles and inhibit performance were identified. In addressing the challenges in the teaching and learning of Social Studies, teachers need to be empowered to address these factors and implement the curriculum effectively. Findings from the data identified a number of possible causes for the underperformance of learnersand recommendations are made to address these problems